Sosialisasi Menabung Sejak Dini di Sekolah Dasar (SD) Negeri 1 Raraa - Kusrawan K (Yayasan Daarul Huda Kruengmane, 2026)
Early savings socialization activities are an effort to instill positive habits and a culture of thrift in elementary school-aged children. This program was implemented at SDN 1, Raraa Village, Ladongi District, East Kolaka Regency. Activities included providing material on the importance of saving and distributing simple savings media to participants.The implementation method was an interactive lecture and question and answer session. The results of the activity showed high participant enthusiasm, increased understanding of the benefits of saving, and the emergence of student commitment to starting a savings habit. Thus, this socialization has a positive impact in developing a thrifty and responsible character in children from an early age.